Nurses with Disabilities : Professional Issues and Job Retention - Neal-Boylan, Leslie (Springer Pub. Co., 2013)
""This book will provide nurses with the information to make objective and fact based assessments ... Moreover, it will arm nursing professionals with an understanding of how the issue of disability is affecting workforce supply in nursing, how accommodations can provide assistance to individuals with disabilities, and how a balanced and thoughtful approach can allow nursing professionals to function to their fullest."". Geraldine Polly Bednash, PhD, RN, FAAN. Chief Executive Officer/Executive Director. American Association of Colleges of Nursing. ""[This book] has brought together information.